Digital Teaching Tools in 21st Century EFL Classroom: Are Our Teachers Ready? - Tono Suwartono; Asfi Aniuranti (Universitas Muhammadiyah Jember, 2019)
Over the past decade, along with the rapid growing information of communicationtechnology, information processing has become an indispensable part ofapplication in variety of fields. In relation to language teaching and learning,digital media has invaded the classroom. Unfortunately, during professionaltraining the writer’s gave, those English teachers who belonged to ‘well prepared’for this sort of media was very few. These teachers used a laptop with certainlearning materials which were prepared prior to teaching and an LCD projectorand/or speakers on the desk. In general, their teaching and learning seemed tobe more interesting due to technology touch. They created an image of beingcreative, and above all, innovative. This paper discusses how technology, in thiscase digital teaching media, supports teaching and learning; then, outlines theproblems facing EFL teachers; and, finally, suggests possible solutions to theproblems. Obviously, this paper is meant to promote professional teaching andcontribute to future researches on similar topic.